Effectiveness of the Pfazer vaccine against COVID-19 patients in chronic diseases. - Jihan Qais Dakhal AL-lamy; Ahmed D. Jabbar (Genius Journals, 2022)
Corona viruses belong in the corona family and are part of the nidovirales order. The family of closed-cell, positive-sense, single-stranded RNA viruses known as coronaviruses (CoVs) possesses a diverse variety of traits. The respiratory, digestive, hepatic, and neurological systems are all affected, and they cause a wide range of health issues in both people and animals. In this study, individuals who received the Pfizer vaccine had their IgG and IL6 levels measured. The study includes 167 cases, They were distributed on the basis of age and sex into four groups, The first group included 47 patients, which is the control group, the second group included 42 patients diseases only, the third group included 39 patients with Covid-19 only, and the fourth group included 39 patients Covid-19 and diseases. The study indicated a significant increase in (p <0.01) in IgG for patients with Covid and chronic diseases with chronic diseases compared to other groups. The study we obtained indicated a significant increase in (P>< 0.01) in IL6 ratio in relation to gender and age groups. According to these findings, the Corona virus may have an impact on and pose a threat to everything that results in the body's critical organs failing
Keywords: Covid 19; IgG Level Measurement; Effectiveness; pfazer